Brand Activism dalam Membangun Brand Trust pada Konsumen Generasi Z di Provinsi Lampung: Studi Kasus Brand Smartphone - Raynaltha, David; Khairudin, Khairudin (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2026)
This study aims to examine the influence of brand activism on brand trust among Generation Z consumers in Lampung Province. Brand activism refers to a brand's active involvement in social, environmental, or political issues that align with consumer values. A quantitative approach was applied using a descriptive-verificative method. A total of 100 respondents were selected through purposive sampling, targeting Generation Z consumers who are active on social media and have engaged with or are aware of brand activism initiatives. Data were collected via an online questionnaire and analyzed using simple linear regression with the help of SPSS software. The results revealed that brand activism has a positive and significant effect on brand trust, as indicated by a t-value of 14.942, which exceeds the t-table value of 1.984, and a significance level of 0.000, which is below 0.05. The regression coefficient of 0.814 suggests that an increase in brand activism activities leads to a 0.814-unit rise in brand trust. Furthermore, the F-test also confirmed the model's significance, with an F-value of 223.270 surpassing the F-table value of 3.94 and a significance level of 0.000. Therefore, it can be concluded that brand activism plays a crucial role in fostering consumer trust, particularly among socially conscious young consumers.